Iron accumulation in tumor-associated macrophages marks an improved overall survival in patients with lung adenocarcinoma - Thielmann, Carl Maximilian; Costa da Silva, Milene; Muley, Thomas; Meister, Michael; Herpel, Esther; Muckenthaler, Martina (Scientific reports, 2019)
Iron-loaded tumor-associated macrophages (iTAMs) show a pro-inflammatory phenotype, hallmarked by anti-tumorigenic activity and an ability to attenuate tumor growth. Here we explored the relevance of these findings in lung cancer patients by investigating the impact of the iTAM content in the tumor microenvironment (TME) on patient survival. We analyzed 102 human non-small cell lung cancer (NSCLC) paraffin-embedded archival tissue samples for iron levels and macrophage numbers. Interestingly, patients with lung adenocarcinoma accumulating iron in the TME show higher numbers of M1-like pro-inflammatory TAMs and a survival advantage compared to iron-negative patients. By contrast, in patients with lung squamous cell carcinoma iron in the TME does not affect survival, suggesting a unique influence of iron on different histological subtypes of non-small cell lung cancer (NSCLC). We conclude that in lung adenocarcinoma iron may serve as a prognostic marker for patient survival and as a potential therapeutic target for anti-cancer therapy.